2022
DOI: 10.1101/2022.08.02.502359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Next-generation large-scale binary protein interaction network for Drosophila

Abstract: Generating reference maps of the interactome networks underlying most cellular functions can greatly illuminate genetic studies by providing a protein-centric approach to finding new components of existing pathways, complexes, and processes. Here, we applied state-of-the-art experimental and bioinformatics methods to identify high-confidence binary protein-protein interactions (PPIs) for Drosophila melanogaster. We performed four all-by-all yeast two-hybrid (Y2H) screens of >10,000 Drosophila proteins, resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Decreased and accelerated autophagy in MuSCs leads to similar defects caused by Deaf1 alteration, raising the possibility that Deaf1 may be involved in the regulation of autophagy. In our previous genetic screen, we identified that Deaf1 genetically interacts with Atg1 and that depletion of Deaf1 induces autophagy in larval fat body [18]. Therefore, we investigated if Deaf1 may also regulate autophagy in MuSCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased and accelerated autophagy in MuSCs leads to similar defects caused by Deaf1 alteration, raising the possibility that Deaf1 may be involved in the regulation of autophagy. In our previous genetic screen, we identified that Deaf1 genetically interacts with Atg1 and that depletion of Deaf1 induces autophagy in larval fat body [18]. Therefore, we investigated if Deaf1 may also regulate autophagy in MuSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin Immunoprecipitation was performed on thorax muscle tissues of FOXO-V5;FOXO 25 / FOXO 25 Drosophila (BDSC, 80945) or C2C12 cells, using the Simple ChIP Plus Enzymatic Chromatin IP Kit (Magnetic Beads) (Cell Signaling Technologies, #9005), according to manufacturer's instructions and following the procedures described in our previous paper [18]. Briefly, the C2C12 cells and grinded muscles from FOXO-V5; FOXO 25 /FOXO 25 flies were crosslinked with 1% Formaldehyde and quenched with glycine.…”
Section: Chromatin Immunoprecipitation (Chip)mentioning
confidence: 99%
See 1 more Smart Citation
“…During autophagy, double-membrane vesicles, called autophagosomes, engulf organelles or proteins and subsequently fuse with lysosomes to degrade the contents within the autolysosomes [ 14 ]. This process is strictly regulated by multiple autophagic regulators such as mTORC1, TRAF6, AMPK, ZIPK, TFEB, FOXO, Dwg, and P53 [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Autophagy has been reported to play different roles during various stages of tumor development.…”
Section: Introductionmentioning
confidence: 99%